Estudo biológico e biossintético com alvo nas amidas pirrolidínicas de Piper arboreum Aublet (Piperaceae) - Pinto, Rute Alves [UNESP] (2015)
Piper arboreum is known to accumulate amides with potential antitumoral, antimicrobial, antifungal, antileishmanial and insecticidal activities, being targeted compounds for biosynthetic studies. From leaves and fruits extracts, three pyrrolidinic amides and two phenylpropanoids precursors were isolated and the piperilina amide was used as standard for biosynthetic studies. The biosynthetic proposal for piperiline precusors formation follows a mixed biosynthesis, which is derived from the shikimate and acetato are which C6-C3 units which condense with malonyl-CoA and ornithine for the production of the amides. The biosyntetic studies were initiated with the incorporation of CH313CO2Na in leaves of P. arboreum. Analysis by mass spectrometry confirmed incorporation of 13C isotope indicating that extention chain of piperilina is product via acetate. To determine formation of the methylenedioxy group occurs before or after the amide portion, were if the synthesized phenylpropanoids precursors ferulic acid and 3',4'-methylenedioxycynamic acid as well the same compounds labeled with stable isotopes: [1-OD, 2-D]-ferulic acid and [1-OD, 2-D]- 3',4'-methylenedioxycynamic acid. The synthetized labeled precursors were incorpored into the soluble fraction of the enzymatic extraction, together with precursors L-ornithine and malonic acid. The products were analyzed by liquid chromatography and mass espectrometry using piperline amide as standard. Analysis of the protein extract from de leaves and fruits using 1D polyacrylamide gel allowed to assing the most significant bands: the RuBisCo (55 - 14 kDa), PAL (77- 83 kDa) and PKS (45 - 30 kDa) enzimes. The piperiline amide isolated from P. arboreum were submetted to inativation assay of the enzyme tyrosinase and showed powerful in vitro activity. The etanolic extracts from leaves from P. arboreum showed important antifungal, anti-inflammatory and inseticidal...